A new device to measure load and motion in lower limb prosthesis - Tested on different prosthetic feet - Schuy, J.; Burkl, A.; Rinderknecht, S.; Beckerle, Philipp (2014 IEEE International Conference on Robotics and Biomimetics, IEEE ROBIO 2014, 2014)
In this work, a new system is presented to measure load and motion in six degrees of freedom synchronously to assess amputee gait in real time. The device is integrated in the shank of lower limb prostheses to measure the gait parameters based on a combination of AHRS (Attitude Heading Reference System) and a strain gauge pylon. This novel mobile and autonomous system enables new possibilities of amputee gait assessment by gathering both kinds of data. After a presentation of the system, two approaches to calculate the 6×6 calibration matrix of the strain gauge pylon with respect to main channels and cross talk channels are presented and compared. Finally, the data analysis process, a performed pilot study of a transfemoral amputee wearing two different prosthetic feet and consequent load results are discussed.
CRIS-Team Scopus Importer:2021-09-24